The impact of coronavirus disease 2019 (COVID-19) pandemic experiences on attitudes towards vaccinations: on the social, cultural and political determinants of preferred vaccination organization models in Poland - Piotr Żuk; Paweł Żuk (BMC, 2024)
Abstract Background The article describes attitudes towards vaccinations in Poland in relation to issues such as voluntary versus compulsory vaccinations, the method of financing vaccinations, the method of organizing and carrying out vaccinations, the cognitive and educational aspect of vaccines (how to obtain knowledge about vaccines) and the preferred model of work and research on new vaccines. Taking into account these issues, the authors have created four ideal models of preferred vaccination policies: (a) the market model; (b) the state model; (c) the vaccine hesitancy model; and (d) the civic-social model. This perspective makes it possible to better understand and learn about the various motives behind the attitudes of anti-vaccination movements, as well as to notice cracks and divisions among vaccination supporters and their attitudes towards the financing and organization of vaccinations. Methods The study was carried out using the CATI method on a representative random-quota sample of Polish society of 1000 people aged 18 and over. The study took age, sex, education and the size of the place of residence into account. Additionally, in the Socio-demographic factors influencing attitudes towards vaccination practices in Poland section, we used the chi-squared test and regression analysis of factors influencing vaccination practices in Poland. PASW Statistics 18 (a version of SPSS) software was used for statistical analysis. Significant correlations were demonstrated at a significance level of 0.05% Pearson. Results This article has shown that attitudes towards vaccinations are embedded in broader divisions and orientations related to the vision of the social order: the role of the state, the organization of healthcare and payments for vaccinations and medical services, as well as preferred ways of knowledge production in society and work on new vaccines. The political sympathies and the age of the respondents were the most important variables influencing vaccination behaviour. The education of the respondents was less important. Conclusions A few years after the peak of the pandemic, the scope of anti-vaccination attitudes in Polish society ranges from 20% of the population (dogmatic anti-vaxxers) to 30% (vaccine hesitancy occurring depending on attitudes towards vaccinations).